HE PROSPECTS OF RAINWATER HAVESTING IN HO CHI MINH CITY - Lan Chi, Nguyen Thuy; Dao, Phan (GeoScience Engineering, 2016)
Wisely using of natural water resources to serve human needs plays a decisive role in ensuring water and food security. In the natural water cycle, rainwater is considered as a valuable renewable resource. Rainwater harvesting (RWH) for daily life and production is simple but effective and also environmentally sound measure. This one is also a positive solution in climate change adaptation strategy. However this resource are being wasted in our country in general and in HCM City in particular. This paper overviews the status of rainwater use in the world; the general situation, the potential of rainwater collection and a number of issues related to the potential of rainwater harvesting in the city. Some solutions to enhance the use of rainwater and improve water supply for city residents also suggested in this discussion.